RAILTOPOMODEL AND RAILML 3 IN OVERALL CONTEXT - Adam Hlubuček (Acta Polytechnica CTU Proceedings)
This paper aims to provide a brief insight into the UIC RailTopomodel and railML initiative. Concerning the railML exchange format, mainly the current form of forthcoming third edition, involving especially the infrastructure schema, based on the RailTopoModel modelling principles, is taken into account. When rewarding, the comparison between railML 3 and the previous railML 2.3 version is given. At the end, the author focuses on selected issues of possible applicability of these tools for the needs of such systems as the automatic train control, automatic train operation, prediction of train etc. If essential, some extensions of the structures are proposed.